2015
DOI: 10.1007/s00068-015-0554-4
|View full text |Cite
|
Sign up to set email alerts
|

Internal versus external fixation of the anterior component in unstable fractures of the pelvic ring: pooled results from a systematic review

Abstract: Internal fixation of the anterior pelvic ring as supplementary fixation for unstable injuries to the pelvic ring appears to result in better radiographic and functional outcomes as well as fewer complications. However, data that separated outcomes and complications in relation to interventions of the anterior pelvic ring were limited. More studies looking specifically at outcomes in relation to the type of anterior ring intervention are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…The external fixator was preferred for the anterior ring, by four of the seven hospitals. The external pelvic fixator has been reported as a valuable tool for the elderly 43 , but it may be complicated by frequent loosening or pin tract infections 44 , 45 . Retrograde transpubic screw fixation has yielded good results in terms of fracture reduction and healing, with only a small number of adverse events (17 of 128 cases) reported by a large retrospective series 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The external fixator was preferred for the anterior ring, by four of the seven hospitals. The external pelvic fixator has been reported as a valuable tool for the elderly 43 , but it may be complicated by frequent loosening or pin tract infections 44 , 45 . Retrograde transpubic screw fixation has yielded good results in terms of fracture reduction and healing, with only a small number of adverse events (17 of 128 cases) reported by a large retrospective series 46 .…”
Section: Discussionmentioning
confidence: 99%
“…For the anterior ring, Vaidya [18,26] suggested INFIX indications included superior ramus pubis, inferior ramus pubis, and bilateral ramus pubis fractures. All 17 patients in this group received an INFIX fixator and one successful screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…For anterior ring injury, traditional fixation methods include external fixation, open reduction plate fixation, X-ray guidance for ramus screw fixation, and open Stoppa approach surgery [18]. The INFIX, a new minimally invasive method for the treatment of unstable pelvic fractures, was described in 2011 with little trauma and little impact on patients' daily activities [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since the presented data reflect only short-term results, the status cannot be evaluated after healing. A meta-analysis for this problem concluded that internal fixation of the anterior pelvic ring as supplementary fixation for unstable injuries of the pelvic ring resulted in better radiographic and functional outcomes as well as fewer complications 19 , but clear inclusion criteria regarding the quality of the studies, the type of fractures treated, the kind of osteosynthetic fixation or the follow-up period were not defined. A quantitative analysis based on this unreliable data set is fairly misleading and not suitable as a basis for treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%